2014
DOI: 10.4187/respcare.03470
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation With a Single Portable Pulse-Dose Oxygen-Conserving Device and Combined Stationary and Portable Oxygen Delivery Devices in Subjects With COPD

Abstract: BACKGROUND: Portable oxygen devices simplify and facilitate patient therapy. This study was designed to compare S pO 2 and patient satisfaction with a portable oxygen concentrator or a combined system consisting of a fixed device with continuous-flow oxygen dispensation and a portable device with pulse dispensation for ambulation. METHODS: This crossover trial assessed 25 subjects with COPD (92% men, mean age of 72.2 ؎ 7.4 y, mean FEV 1 of 34.14 ؎ 12.51% of predicted) at 4 hospitals in Madrid. All subjects had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“… 3 , 4 A recent study showed that chronic obstructive pulmonary disease (COPD) patients requiring LTOT generally prefer a single source POC over a combined stationary and portable oxygen source both in the home and during activity, citing the practicality of the system as its main advantage. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 A recent study showed that chronic obstructive pulmonary disease (COPD) patients requiring LTOT generally prefer a single source POC over a combined stationary and portable oxygen source both in the home and during activity, citing the practicality of the system as its main advantage. 5 …”
Section: Introductionmentioning
confidence: 99%
“…But as noted by Chatburn et al [24], a key consideration in achieving efficacious therapy of any oxygen therapy “is not whether a person desaturates at night, but why they desaturate”. And despite the controversy, the ambition for the POC category is evolving towards a single-device for home and ambulation, as experience grows with nocturnal pulsed oxygen delivery and in response to user preference [24, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, POCs alone did not supply the same levels of oxygenation as the combination of fixed and portable systems. 17 Furthermore, as described by McCoy 1 and others, 18 it is not clear how the wide variety of models and setting available on modern POCs affect patient oxygenation and adherence. Thus, we believed that a fundamental study of the interaction of patient physiology with the output of a real POC could provide guidance for future developments in device design and patient management.…”
Section: Discussionmentioning
confidence: 99%